Pengembangan LKPD Pembelajaran Tematik di Kelas V Sekolah Dasar Kota Bengkulu - Gusti Kristia Ningrum; Sri Dadi; Victoria Karjiyati (Universitas Bengkulu, 2020)
This study aims to develop thematic learning LKPD in class V Elementary School Bengkulu City. This study is a Research and Development (R&D) research by modifying the 4-D model. This research was conducted in three stages, namely define, design, and develop. The instrument used in this study was a LKPD validation sheet. Data analysis techniques used descriptive statistical analysis of expert validation assessments, teacher responses, and student responses. This study resulted in the development of thematic learning LKPD with an assessment of the LKPD experts for 89.47 categories very good, teacher responses of 90 categories very good, and student responses of 92.5 with very good categories. The conclusion of this study is to produce a thematic learning LKPD development product suitable for use in class V Elementary Schools of Bengkulu City. Keywords: LKPD, Development, Thematic